THE PROCESS OF DEHUMANIZATION IN THE CONTEXT OF THE SOCIAL CHARACTER AND IDEOLOGY OF THE GLOBALIZED SOCIETY - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article examines the reasons for reproduction and authorization of a "Dionysian" beginning in the spiritual space of the modern globalized society; also it investigates the causes of the material and social manifestations over socio-psychological process of dehumanization that is typical for our time.